2013
DOI: 10.3390/polym5041215
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Molecularly Imprinted Polymer as SPE Sorbent for Melamine Isolation

Abstract: Abstract:In this paper, a separation procedure combining molecularly imprinted-solid phase extraction (MI-SPE) was developed for the isolation of melamine. The molecularly imprinted polymer (MIP) was prepared using precipitation polymerization method where melamine as template, 9-vinylcarbazole as functional monomer, ethtylene glycol dimethacrylate as a cross-linker and benzoyl peroxide as initiator. An off-line MI-SPE method followed by ultra-performance liquid chromatography detection of melamine was establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 18 publications
0
47
0
3
Order By: Relevance
“…The k' value for Py-IP is 2.2617, which represents a good selectivity towards pyrogallol (Yusof et al, 2013;Liu et al, 2004). This shows that the binding cavities has successfully been imprinted in Py-IP.…”
Section: Selectivity Studymentioning
confidence: 77%
See 1 more Smart Citation
“…The k' value for Py-IP is 2.2617, which represents a good selectivity towards pyrogallol (Yusof et al, 2013;Liu et al, 2004). This shows that the binding cavities has successfully been imprinted in Py-IP.…”
Section: Selectivity Studymentioning
confidence: 77%
“…It was determined by the value of relative selectivity (k'). The value of k' must >1 to consider the imprinted polymer to be acceptable and to have a good selectivity towards the target molecule (Yusof et al, 2013;Liu et al, 2004). Results showed that the value of k' for Py-IP was >1, which indicated that Py-IP was successfully imprinted and had a good selectivity towards Py.…”
Section: Discussionmentioning
confidence: 99%
“…The two obvious bands appearing at 2870 and 2920 cm −1 due to the C‐H stretching vibrations also confirm the functionalization of the modified Fe 3 O 4 @SiO 2 with ClPTMS, which was designated as Fe 3 O 4 @SiO 2 @CPTMS (Figure c) . In the FT‐IR spectrum of Fe 3 O 4 @SiO 2 @PTMS@Melamine, two new peaks appeared at 1625 and 1541 cm −1 are due to melamine C=N stretching and N‐C‐N bending vibrations (Figure d) . Based on these bands, successful grafting of melamine onto the Fe 3 O 4 @SiO 2 @CPTMS nanoparticles surface is concluded.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting MIP serves high specificity and selectivity for the template, and is favorable towards mechanical, thermal, and chemical stabilities [1,2]. It is clearly suitable for various applications, such as in separations [3], chemical sensors [4], selective catalysis [5], and hybrid membranes [6].…”
Section: Introductionmentioning
confidence: 99%